378. FLOT VS ECX: A COMPARISON OF TWO NEOADJUVANT CHEMOTHERAPY REGIMEN'S EFFECTS ON SARCOPENIA IN ESOPHAGOGASTRIC ADENOCARCINOMA PATIENTS. (24th September 2022) - Convill, James; Chmelo, Jakub; Prasad, Pooja; Brown, Joshua; Petrides, George; Phillips, Alexander
Abstract: Sarcopenia is defined as a loss of skeletal muscle mass and function. It is prevalent amongst patients with esophagogastric adenocarcinoma (EGA) and associated with adverse treatment outcomes. Neoadjuvant chemotherapy (NAC) may contribute to sarcopenia development. FLOT, although superior to ECX in terms of survival, has been reported to have higher toxicities. The aim of this study was to compare the effect of ECX and FLOT on sarcopenia and lean body mass (LBM) in EGA patients. Patients diagnosed with EGA between January 2017 and December 2020 and undergoing ECX/FLOT NAC followed by esophagectomy from a single tertiary center in the UK had their pre- and post-NAC CT scans assessed for radiological sarcopenia. Skeletal muscle index (SMI) was calculated from muscle area measured on CT scans at the level of third lumbar vertebra. Previously published SMI cut off values for radiologically defined sarcopenia were used (52.4cm 2 /m 2 for men and 38.5cm 2 /m 2 for women). LBM (kg) was calculated using a previously published formula. 153 patients were included in the analysis. Sarcopenia increased from 77/153 (50.3%) pre-NAC to 98/153 (64.1%) post-NAC (p < 0.005). There were 48/82 (58.5%) ECX and 29/65 (44.6%) FLOT patients sarcopenic pre-NAC. 60/82 (73.2%) ECX and 38/65 (58.5%) FLOT patients were sarcopenic post-NAC and pre-operatively. There was no statistically significant difference observed for development of sarcopenia after NAC between the two NAC regimens (p = 0.793). Similarly, LBM significantly decreased during NAC (p = 0.007), but this effect did not vary between NAC regimen (p = 0.917). Radiological sarcopenia is highly prevalent in EGA patients and significantly increases during NAC. However, this study suggests that there is no difference in the degree of sarcopenia between ECX and FLOT NAC regimens. Impact of pre- and post-FLOT related sarcopenia on treatment outcomes needs to be established alongside strategies to treat this syndrome and prevent its further development.